A nomogram for predicting progression-free survival in stage III–IV gastric cancer based on post-treatment cholinesterase and C-reactive protein - Hu, Dan; Wang, Yumin; Zhang, Yongjie (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Serum cholinesterase (CHE) and C-reactive protein (CRP) are established prognostic markers in gastric cancer, but their levels after two cycles of therapy are rarely incorporated into predictive models. This study aimed to develop a nomogram integrating post-treatment CHE and CRP levels after two cycles of first-line therapy to predict progression-free survival (PFS) in patients with stage III–IV gastric adenocarcinoma.Methods: This retrospective study included 104 treatment-naïve patients with stage III–IV gastric adenocarcinoma who received first-line therapy. Serum CHE and CRP were measured after two cycles. Optimal prognostic cut-off values were determined by maximally selected rank statistics and validated via bootstrap resampling. Independent prognostic factors were identified by Cox regression to construct a nomogram. Model performance was evaluated using the concordance index (C-index), calibration plots, time-dependent receiver operating characteristic (ROC) analysis, and decision curve analysis (DCA). Overfitting was quantified by repeated K-fold cross-validation. Public transcriptomic data were analyzed via gene set variation analysis (GSVA) to explore associated pathways.Results: Optimal cut-off values were 4,865 U/L for CHE and 2.58 mg/L for CRP, confirmed by bootstrap validation. Multivariate analysis identified low post-treatment CHE (≤4,865 U/L) as an independent protective factor for PFS [hazard ratio (HR) =0.36; 95% confidence interval (CI): 0.20–0.63; P2.58 mg/L) (HR =1.67; 95% CI: 0.99–2.84; P=0.06) and peritoneal metastasis (HR =1.66; 95% CI: 0.93–2.95; P=0.09) were associated with increased risk. The nomogram achieved a C-index of 0.709 (95% CI: 0.652–0.766), improving to 0.751 after cross-validation adjustment. Time-dependent ROC yielded areas under the curve (AUCs) of 0.789, 0.836, and 0.760 for 6-, 12-, and 18-month PFS, respectively. Risk stratification based on nomogram scores revealed significantly poorer PFS in the high-risk group (P